Investimento e expectativas de política monetária no contexto do regime de metas para a inflação - Luis Alberto Pelicioni (2007)
The main purpose of this dissertation was analyse the relation between monetary policy and investment in the context of the inflation target system taking into account the different theoretical paradigms emphasized by mainstream and post-keynesians approaches. An investment equation was estimated using the panel data methodology to seventeen countries that adopt inflation target system, and a proxy for current expectations about monetary policy was adopted as one of the independent variables of the equation. A dummy piece-wise variable was inserted to test structural break hypothese on the coefficient of the proxy variable after the inflation target system implementation. The results highlight that a negative correlation between current expectation of restrictive monetary and current investment rose after the inflation target system implementation. An specific time series investment equation for the Brasilian economy was estimated. These results support the post-keynesian approach.